Clinical analysis of pediatric patients who visited Masan Samsung Emergency Center - Jae Wook Yoo; Jun Hwa Lee (Korean Pediatric Society, 2010)
Purpose : Through a clinical and retrospective analysis of pediatric patients who visited the Regional Emergency Medical Center of Masan Samsung Hospital from January 2007 to December 2008, we characterized pediatric and adolescent emergency patients to improve emergency care in future. Methods : We reviewed the medical records of 14,065 pediatric patients below 19 years of age. Results : The male to female ratio was 1.5:1, and the most common age group was less than 3 years (49.6%). The peak month was May (10.0%), the peak day of the week was Sunday (24.7%), and the peak time of day was 20:00–20:59 (8.5%). There was no difference in the number of visits per day based on weather (sunny, rain [below 10 mm per day], snow, and fog) or daily temperature difference; however, visits increased on sandy, dusty days and decreased on rainy days with more than 10 mm of rain per day. Based on the international classification of disease (ICD)-10 system, the most common disease code was code R (symptoms, sign, and abnormal clinical laboratory finding) (31.5%), and the most common symptom was fever (13.1%). Final outcomes were discharged (73.8%), admitted (25.7%), transferred (0.4%), and expired (0.1%). In adolescent patients aged 15–19 years, the most common disease code was Injury & Poisoning (code S&T, 36.9%); the most common symptom was abdominal pain (9.6%). Conclusion : Pediatric patients visiting the emergency center were most likely to be male and under 3 years of age and to visit between 20:00 and 21:00 on Sundays and in May, and the most common symptom was fever. Differences between adolescents and pediatric patients showed that adolescents had a higher visiting rate with abdominal pain and a larger temperature difference.